Kebijakan Pendidikan Khalifah Harun Ar-Rasyid - Tadjuddin, Nilawati; Maulana, Alif (Al-Tadzkiyyah: Jurnal Pendidikan Islam, 2018)
One of the keys to advancing a nation is education. The future of a nation really needs the contribution of the nation's children who are competitive, superior, intelligent and faithful, given that competition is increasingly high in the global era. Indonesia has several problems in the world of education, starting from the low teacher salaries to high dropout rates, ending with the absence of the Indonesian education system in the list of 20 countries with the best education systems in the world. Islam itself in the field of education had enjoyed periods of glory when the Abbasid dynasty came to power. The fifth caliph's policy, Harun Ar-Rasyid, which at that time concentrated on improving the quality of education, made this period worthy of being dubbed the golden age of Islam (the Islamic Golden Age). The education policy that Ar-Rasyid applied could certainly be a solution to solve various problems that are currently sweeping the world of Indonesian education. This study focuses on the educational policies adopted by Caliph Harun Ar-Rasyid during the golden age of Islam. Through the literature study method, this study confirms that by studying history, all problems that are sweeping the world of education in this country can be resolved, and figures like Ar-Rasyid are the most appropriate to be asked for a solution.